Hierarchical structure of carbon nanotube fibers, and the change of structure during densification by wet stretching. (September 2018) - Cho, Hyunjung; Lee, Haemin; Oh, Eugene; Lee, Sung-Hyun; Park, Junbeom; Park, Hyun Jin; Yoon, Suk-Bae; Lee, Cheol-Hun; Kwak, Gye-Hoon; Lee, Won Jae; Kim, Juhan; Kim, Ji Eun; et al.
Abstract: Carbon nanotube (CNT) fibers were strengthened by wet stretching with 1-Methyl-2-pyrrolidinone (NMP) or chlorosulfonic acid (CSA) as the wetting liquid, and the change of hierarchical structure of CNT fibers was observed at a nanometer level. Two kinds of voids were present in a CNT fiber: inter-bundle void and intra-bundle void. Wet stretching was a very effective method to aggregate CNT bundles and to remove the voids in a CNT fiber. CNT bundle thickness and the number of CNTs in a bundle increased and the bundle-to-bundle distance decreased as a result of the aggregation of the bundles. After infiltration of liquids, CNTs with elliptical and non-circular cross-sections appeared and the distance between CNTs in a bundle i.e., intra-bundle voids, decreased. It was confirmed that the stretch alone did not affect the intra-bundle void. CSA infiltrated CNT bundles better than NMP did, so CSA yielded better densification than NMP. Load at failure, specific strength ( SS ) and tensile strength of CNT fibers increased with wet-stretching. SS of the CNT fiber increased from 0.95 to 2.19 N/tex ( CSA13% ). Understanding structure and morphology of CNT fibers in nanoscale will be helpful to build better strengthening strategies. Graphical abstract: Image 1